2020
DOI: 10.1038/s41598-020-77464-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences of sucrose accumulation concentration and related genes expression between two sucrose accumulation types of Actinidia eriantha

Abstract: According to the investigation of wild Actinidia eriantha in Jiangxi province of China, we found that soluble solids content of fruit was lower than edible standard (14%). However, we found a high-sugar type A. eriantha line (code was ‘MM24’, test material) during investigative process at Nancheng county (E 116° 48′, N 26° 23′, 845 m). We sheared its scions to asexual reproduction in Fengxin County (rootstock was A. deliciosa ‘Miliang 1’ with 7 years old) and at the same time DUS (Distinctness, Uniformity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Fruit maturation is a complex physiological process, which is accompanied by a series of biochemical processes such as sugar accumulation (Zhang Y.J. et al, 2014;Xu et al, 2020), acid reduction (Jiang et al, 2020), aroma production (Wei et al, 2016), pigment accumulation (Gan et al, 2019), flavonoid metabolism (Huang et al, 2020), and endogenous hormone change (Wang et al, 2016). The difference of fruit quality between early mature and late mature cultivar in our study was mainly reflected in the SSC, DM, and pigment contents.…”
Section: Discussion Low Concentration Of Endogenous Hormones Promote Starch Hydrolyzed To Sugarsmentioning
confidence: 52%
“…Fruit maturation is a complex physiological process, which is accompanied by a series of biochemical processes such as sugar accumulation (Zhang Y.J. et al, 2014;Xu et al, 2020), acid reduction (Jiang et al, 2020), aroma production (Wei et al, 2016), pigment accumulation (Gan et al, 2019), flavonoid metabolism (Huang et al, 2020), and endogenous hormone change (Wang et al, 2016). The difference of fruit quality between early mature and late mature cultivar in our study was mainly reflected in the SSC, DM, and pigment contents.…”
Section: Discussion Low Concentration Of Endogenous Hormones Promote Starch Hydrolyzed To Sugarsmentioning
confidence: 52%
“…It was reported that strong light cooperation could accumulate more sucrose in watermelon [45]. In Ganlv 1, the relative expression level of AcSPS5 gene was significantly high in the later stage of fruit development [48]. In cucumber, extensive metabolism of stachyose occurred in fruit peduncles [45].…”
Section: Discussionmentioning
confidence: 98%
“…Fructose and glucose are monosaccharides, while only sucrose is disaccharide. However, the accumulation process of sugar is very complicated [48]. Based on previous studies, we identified the expression of SS4 and SS3 gene in cucumber seed.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the nutrient composition is essential for conventional breeding. Previously, studies on the evaluation of nutrient components of A. eriantha were mainly investigated using simple measuring methods such as HPLC (High performance Liquid Chromatography) [ 2 , 3 , 4 , 12 ]. In this study, the nutrient components of three A. eriantha lines were investigated using UPLC-MS/MS methods, which have been used for nutrient evaluation in A. chinensis kiwifruit [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose and fructose are the main soluble sugars in A. deliciosa , A. rufa and A. eriantha fruits, while sucrose is the primary sugar in A. argute [ 10 , 32 ]. Previous studies have addressed the dynamic changes in starch and soluble sugar levels and gene expression that occur during kiwifruit development and ripening stages, with SPS, SPP, AGPases related to the synthesis of sucrose and starch, and SUS, FK, and HK related to metabolism reported [ 12 , 13 , 33 ]. The organoleptic properties of the fruit are determined by the type and content of soluble sugar and organic acid.…”
Section: Introductionmentioning
confidence: 99%